2012
DOI: 10.1007/s10856-012-4699-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on the properties of SiO2–CaO–MgO–P2O5 bioactive glasses

Abstract: Since the invention of 45S5 Bioglass, researchers never stopped exploring new generation bioactive glass (BG) materials for wider applications in regenerative medicine, among which a novel SiO(2)-CaO-MgO-P(2)O(5) bioactive glass (BG20) is an excellent candidate. However, apart from their biocompatibility and bioactivity, a porous structure is also a must for a tissue engineering scaffold in successfully fixing bone defect. The porosity is the outcome of the high temperature (500-1,000 °C) treatment in the fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Chang and coworkers 141 fabricated a novel SiO 2 –CaO–MgO–P 2 O 5 bioactive glass (BG20), reporting an advanced technique based on heat-treating to create BG20 powders with different crystallization structures. In vitro studies showed cell proliferation using mouse fibroblast (NIH3T3) and BMSCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang and coworkers 141 fabricated a novel SiO 2 –CaO–MgO–P 2 O 5 bioactive glass (BG20), reporting an advanced technique based on heat-treating to create BG20 powders with different crystallization structures. In vitro studies showed cell proliferation using mouse fibroblast (NIH3T3) and BMSCs.…”
Section: Methodsmentioning
confidence: 99%
“…Heat treatment of BG20 (bioactive glass) scaffolds modified the percentage of crystallization changing their mechanical strength, biodegradability and bioactivity. 141 Compressive strength of the TiO 2 scaffolds improved using multiple recoating processes. 196 Mechanically adaptive structures can be manufactured by the crucible melt extraction (CME) process and sintering of MgY4 fibers.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…BG is a traditional biomaterial which has been safely applied in dentistry for a long time. It has been reported that the ions released from BG could in certain extent form a favorable Journal of Biomaterials and Nanobiotechnology microenvironment for the differentiation of the BMSCs [15]. BG can form a carbonated apatite layer between hard and soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason the flowability of WR powder as represented by the Hausner ratio is much higher (lower Hausner ratio) due to its coarser particle size and round morphology of its agglomerates. An approximate flowability 7 threshold for free-flowing powders in terms of Hausner ratio is about 1.25 [16]. Thus the flowability of the finer DR powder (DR 63) is limited.…”
Section: Feedstock Characterisationmentioning
confidence: 99%
“…To obtain bioactive glass powders there are two well extended techniques: melting and subsequent crushing of a (usually) crystalline powder mixture and the sol-gel technique [6,7]. When the sol-gel method is used, the starting materials are processed at lower temperature giving rise to bioactive glasses that exhibit higher bioactivity and biodegradability in comparison with glasses obtained by the melting procedure [8,9].…”
Section: Introductionmentioning
confidence: 99%